The Relationship Between Communication and Teamwork with The Learning Outcomes of Physical Education, Sports and Health - Ganjar Nugraha; Yusuf Hidayat; Burhan Hambali (Journal of Physical Education Health and Sport, 2026)
This research is motivated by the fact that student involvement in Physical Education, Sports, and Health (PE) learning is still not optimal, especially in the aspects of communication and teamwork that have the potential to affect learning outcomes. The purpose of this study is to find out the relationship between communication skills and teamwork on student learning outcomes. The research uses a quantitative approach with a correlational descriptive method. The research subjects consisted of 90 grade VII of Junior High School 12 Bandung who were selected using a simple random sampling technique based on certain criteria. Data collection was carried out through a Likert scale questionnaire that has been adjusted to the context of Physical education learning. Data analysis uses descriptive and inferential statistics. The normality test showed that not all variables were normally distributed, so the analysis was continued using the Spearman Rank correlation test. The results showed that communication had a significant and strong relationship with learning outcomes (r = 0.759; p < 0.05), while teamwork had a very strong relationship (r = 0.830; p < 0.05). Simultaneously, communication and teamwork also showed a very strong association with learning outcomes (r = 0.818; p < 0.05). These findings indicate that teamwork has a more dominant role than communication, especially in PE learning based on group activities. Communication serves as the basis for information delivery and coordination, while teamwork strengthens the process of interaction, role-sharing, and student engagement. Thus, it can be concluded that communication and teamwork are two aspects that complement each other and need to be developed simultaneously to improve student learning outcomes in Physical education learning.